THE CORRELATION BETWEEN THE STUDENTS’ VOCABULARY MASTERY AND THEIR SKILL IN WRITING A SHORT TEXT AT THE SECOND SEMESTER STUDENTS OF COUNSELING DEPARTMENT OF ACHMAD YANI UNIVERSITY - Helmi (Pahlawan Jurnal Pendidikan-Sosial-Budaya, 2019)
This research is purposed to analyze the correlation between students’ vocabulary mastery and their skill in writing a short text at the second semester of counseling department of Achmad Yani University. In this research, the writer used quantitative method by Pearson correlation product moment. There are two variables in this research. Students’ vocabulary as independent variable (variable X) and writing ability as dependent variable (variable Y), the technique of collecting data was by using a test. The test consists of 22 items of vocabulary test and 1 item of writing ability. The object of study is 10 students from the second semester of counseling department of Achmad Yani University. From the calculation by using product moment formula, it was found out that the mean of the scores of the vocabulary test is 67,6. The mean of the scores of the students’ achievement in writing mastery is 67,8. The result of applying the rxy (r count) distribution shows that the coefficient correlation is 0.777. The degree of significance 5% is 0.632 and the degree of significance 1% is 0.765. It means r count is higher than r table (0.777 lebih besar 0.632) and (0.777 lebih besar 0.765). So, alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. The conclusion of this research is there is a significant correlation between students’ vocabulary mastery and their writing a short text ability.